2019
DOI: 10.1149/2.0031911jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—A Method to Measure Extremely Low Corrosion Rates of Copper Metal in Anoxic Aqueous Media

Abstract: In some anoxic aqueous environments, especially in underground nuclear waste repositories, the thermodynamic stability of copper is disputed. This communication presents how a highly sensitive H 2 detector may be used to define an upper bound of the rate of copper corrosion in anoxic aqueous media. Preliminary results are shown for pure water and 0.25-5.0 mol kg −1 NaCl solutions at 30 -75 • C. The results are interpreted to provide maximum corrosion rates to directly support safety assessments for geological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…By presuming that all hydrogen released is from corrosion, as per reactions (1)–(3), a conservative bounding anoxic copper corrosion rate is determined using a highly sensitive solid state ceramic hydrogen probe with a detection limit as low as 0.1 nm/a, or based on more recent publications, 0.01 nm/a. [ 27 ] Within this study, the approach by Senior et al [ 26 ] has been adopted. 2normalCutruenormal(normalstruenormal)normal+H2Otruenormal(normalltruenormal)normal→normalCu2Otruenormal(normalstruenormal)normal+H2(g), Cunormal(normalsnormal)normal+normalynormalH2Onormal(normallnormal)normal→HxCuOynormal+(italicynormal−x2)H2normal(normalgnormal), normalCunormal(normalsnormal)normal+H2Onormal(normallnormal)normal+italicxnormalClnormal(aqnormal)normal→CuClitalicxnormal(aqnormal)normal+normalOHnormal(aqnormal)normal+12normalH2false(normalgfalse).…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
See 2 more Smart Citations
“…By presuming that all hydrogen released is from corrosion, as per reactions (1)–(3), a conservative bounding anoxic copper corrosion rate is determined using a highly sensitive solid state ceramic hydrogen probe with a detection limit as low as 0.1 nm/a, or based on more recent publications, 0.01 nm/a. [ 27 ] Within this study, the approach by Senior et al [ 26 ] has been adopted. 2normalCutruenormal(normalstruenormal)normal+H2Otruenormal(normalltruenormal)normal→normalCu2Otruenormal(normalstruenormal)normal+H2(g), Cunormal(normalsnormal)normal+normalynormalH2Onormal(normallnormal)normal→HxCuOynormal+(italicynormal−x2)H2normal(normalgnormal), normalCunormal(normalsnormal)normal+H2Onormal(normallnormal)normal+italicxnormalClnormal(aqnormal)normal→CuClitalicxnormal(aqnormal)normal+normalOHnormal(aqnormal)normal+12normalH2false(normalgfalse).…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
“…Copper corrosion in anoxic pure water has been discussed for decades, owing to the publication of some results by Hultquist et al, which claimed to have demonstrated copper corrosion in systems for which conventional thermodynamics knowledge would forbid it. [20][21][22][23][24][25] To overcome any debate about these thermodynamics, recent work by Senior et al [26] quantifies anoxic copper corrosion based on detecting the very small amount of hydrogen that is released by high surface area copper in anoxic systems. By presuming that all hydrogen released is from corrosion, as per reactions (1)-(3), a conservative bounding anoxic copper corrosion rate is determined using a highly sensitive solid state ceramic hydrogen probe with a detection limit as low as 0.1 nm/a, or based on more recent publications, 0.01 nm/a.…”
Section: The Anoxic Corrosion Of Copper In Water and Concentrated Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest averaged uniform corrosion rate was equivalent to 0.21 nm/year over a 2‐week period, considerably less than the sustained 0.8 nm/year reported earlier. [ 14,33 ] This may be due, at least in part, to the improved temperature control of the current experimental configuration. The cumulative hydrogen corresponds to the oxidation of only a fraction of a monolayer, a temporary surface effect at best.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10–13 ] Other experiments, including the ones by the current authors, have observed behaviour that may be consistent with corrosion in pure water and brine solutions, as hydrogen released from copper can be detected, albeit at rates that are not considered deleterious to a UFC. [ 14 ] However, the source of hydrogen, be it corrosion or desorption of pre‐existing hydrogen from the copper, is not clear. [ 15,16 ]…”
Section: Introductionmentioning
confidence: 99%